Unifying acoustic emission and digital imaging observations of quasi-brittle fracture. (October 2019) - Lin, Qing; Wan, Bin; Wang, Yan; Lu, Yunhu; Labuz, Joseph F.
Highlights: Acoustic emission (AE) and digital image correlation (DIC) were used for observations. Complementary information by AE and DIC characterizes the fracture process zone (FPZ). Energy evaluation by AE and DIC is consistent with a linear softening law for the FPZ. The FPZ length of sandstone is about 10 times longer than the maximum grain size. Fracture energy of sandstone is estimated seven times greater than that based on LEFM. Abstract: Acoustic emission (AE) and digital image correlation (DIC) were used to characterize the fracture process zone (FPZ) in Berea sandstone, a quasi-brittle material with a maximum grain size of 1 mm. The complementary techniques of AE and DIC provide information on (i) damage throughout the volume, including AE locations and relative energy, and (ii) detailed DIC measurements of opening displacements associated with the FPZ. Three types of specimens were tested by three-point bending: center notch, smooth boundary, and large radius center notch. Experimental results indicate the following: (1) The length of FPZ is about 10 times longer than the maximum grain size. (2) The evaluation of energy based on the two different measurements, AE and DIC, is consistent with a linear softening law for the FPZ. (3) The fracture energy is estimated to be 120–140 J/m 2, about seven times greater than the fracture energy based on linear fracture mechanics.